Secrets from the heart - Young, Sean D. (Entangled Publishing, 2022)
"Taking over her family's charming and historic Red Rose Inn is a dream for Kira Davis--even if it means the extra stress of knowing the entire Davis clan is watching her every move. But ignoring her family's wishes and hiring too-handsome Franklin Bennett as her temporary new manager might be a huge mistake...given their families' decades-long feud...Yet attraction still sparks between them, proving to ex-army engineer Franklin there's something real beneath the surface. Something hopeful. Something unmistakable. But pursuing Kira could prove dangerous for a man with an uncertain future ...Now Kira and Franklin are caught between an ancient family feud and their feelings for each other. The only way they can love each other is by unraveling the terrible truth about what happened back then...and hope that love is strong enough to mend the break from so long ago." --